Vitamin D intake and stroke incidence in adults - Iis Sulastri; Dittasari Putriana (JHeS (Journal of Health Studies), 2022)
Stroke is one of the non-communicable diseases which becomes a global health problem. One of the micronutrient intakes associated with a risk factor for stroke is vitamin D, in which a deficiency of this vitamin is associated with the incidence of ischemic stroke. Therefore, the objective of this study is to determine the relationship between vitamin D intake and the incidence of stroke in adulthood. The method administered is analytic observational with a case-control design and encompasses 40 respondents aged 20-60 years who are members of the Happy Embung community of Yayasan Stroke Indonesia (YASTROKI) DI Yogyakarta. The sampling technique was purposive sampling in the YASTROKI community in Yogyakarta, the measuring instrument employed was the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data were examined by employing Chi square test with the results that more than one third of the respondents in the case group and the control group possessed less vitamin D intake (40% and 85%). There was a significant association between the intake of vitamin D and the incidence of stroke in adults (p = 0.016). This study concludes that adequate nutritional intake, particularly vitamin D, is one way to reduce the risk of stroke and enhance the quality of life of stroke patients.